Assessment of the relationship between the MLST genetic diversity of Listeria monocytogenes and growth under selective and non-selective conditions - Rosa Rodrigues de Souza, Carolina [UNESP]; Bergis, Hélène; Ng, Patricia; Guillier, Laurent; Félix, Benjamin; Leclercq, Alexandre; Gnanou Besse, Nathalie (Elsevier, 2023)
Listeria monocytogenes can grow under stressful conditions and contaminate various food categories. Progresss in DNA sequencing-based identification methods, such as multi-locus sequence typing (MLST) now allow for more accurate characterization of pathogens. L. monocytogenes MLST genetic diversity is reflected by the different prevalence of the “clonal complexes” (CCs) in foods or infections. Better understanding of the growth potentials of L. monocytogenes is essential for quantitative risk assessment and efficient detection across CCs genetic diversity. Using optical density measurements taken with an automated spectrophotometer, we compared the maximal growth rate and lag phase of 39 strains from 13 different CCs and various food origins, in 3 broths mimicking stresful food conditions (8 °C, aw 0.95 and pH5) and in ISO Standard enrichment broths (Half Fraser and Fraser). This is important as growth could influence risk through pathogen multiplication in food. Besides, enrichment problems could lead to a lack of detection of some CCs. Despite small differences highlighting natural intraspecific variability, our results show that growth performances of L. monocytogenes strains under the conditions tested in selective and non-selective broth do not appear to be strongly correlated to CCs and cannot explain higher CC “virulence” or prevalence.
Keywords: Clonal complex; Growth; Listeria monocytogenes; MLST; Selective enrichment